Lorna Doone - Blackmore R. D. (Penguin Readers Level 4)
A romantic adventure story set in south-west England in the 1600s. John Ridd swears revenge upon the evil Carver Doone who murdered his father. But who is the beautiful young girl he meets in Doone Valley?